Strategies for industrialisation in developing countries - Cukor, György. (London : C. Hurst, 1974)
The book discusses strategies for industrialization in developing countries.
Includes bibliographical references and index.
lje 01/16/2018
Loans
Keywords: Industrial promotion; Industries